Nothing to hide, nothing to fear: The moderating effect of fear on AI empowered technology intention of use - Rilho, Alexandre Marcos Vidreiro (2020)
In today's world, technology enabled by artificial intelligence has been the subject of many myths regarding its hidden functions and the threat it poses to privacy and individual freedom. Fear is a powerful motive for human behavior when facing real or perceived threats. Fear is still poorly studied in the relationship between consumers of smart technology and their intention to use it, namely in the field of consumer technology acceptance within the emergence of AI empowered products. This study aims to explore the role that fear plays in reducing or reinforcing the intention to use technology with artificial intelligence, namely an AI empowered device that has very much become a part of us, the smartphone. With a sample of 211 smartphone users, the results show that fear hampers the willingness to use this technology as regards to social networks, even if its’ use is taken as fun, and that an interface being perceived as easy-to-use positively influences the acceptance of biometrics AI apps by means of a perception of utility.